Pre-eruptive storage conditions and magmatic evolution of the Bora-Baricha-Tullu Moye volcanic system, Main Ethiopian Rift - Tadesse, AZ; Fontijn, K; Caricchi, L; Bégué, F; Gudbrandsson, S; Smith, VC; Gopon, P; Debaille, V; Laha, P; Terryn, H; Yirgu, G; Ayalew, D (Elsevier, 2023)
Bora-Baricha-Tullu Moye is a Late Quaternary volcanic system in the Main Ethiopian Rift, characterised by products of both explosive and effusive volcanic eruptions. The petrological and geochemical characteristics of the volcanic products are investigated using a combination of petrography, major and trace element whole rock analyses and in-situ major element analyses of phenocryst phases, matrix glass and melt inclusions. The bulk rock compositions vary from basalt to peralkaline rhyolite (comendite and pantellerite), and the chemical variability can largely be explained by fractional crystallisation processes with minor crustal assimilation and magma mixing. The dominant mineral phases such as clinopyroxenes and feldspars show a tendency for Fe and Na enrichment respectively from the basalts towards the pantellerites. The comendite and pantellerite deposits show systematic variations towards more evolved glass and mineral composition with the stratigraphy. The combination of thermometry (i.e., clinopyroxene-liquid, feldspar-liquid, olivine-liquid and clinopyroxene-only) and barometry (i.e., clinopyroxene-liquid and clinopyroxene-only) modelling suggests that the basaltic magmas are stored at high temperature (1070–1190 °C) at mid-to-deep-crustal levels (~7–29 km). The peralkaline rhyolite melts are stored at lower temperature (i.e., 805–900 °C for comendite; 700–765 °C for pantellerite) at shallow crustal levels (~4 km). The conditions of pre-eruptive storage as recorded in the comendite and pantellerite rocks in combination with stratigraphic constraints, suggests a progressive temporal evolution of the magma reservoirs to cooler storage temperatures.